2014
DOI: 10.1186/1472-6955-13-10
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional study on factors influencing professionalism in nursing among nurses in Mekelle Public Hospitals, North Ethiopia, 2012

Abstract: BackgroundProfessionalism is defined as the conceptualization of obligations, attributes, interactions, attitudes, and role behaviors required of professionals in relationship to individual clients and to society as a whole. Professionalism attributes include knowledge, spirit of inquiry, accountability, autonomy, advocacy, innovation and visionary, collaboration and collegiality, and ethics. The study assessed level and attributes of professionalism in nursing in Mekelle, Tigray, Ethiopia.MethodsInstitutional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
3
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 12 publications
4
35
3
4
Order By: Relevance
“…These findings are supported by a study on nurses' professionalism in Ethiopia, which reported a significant relationship between professionalism and more years of experience. 32 Nurses who have held their jobs for less than four years are likely to still be adjusting to their working environments, which could have a negative effect on their attitudes compared to senior nurses who are more acclimated to their working environments. Nurse leaders may therefore need to be aware of the need to nurture new nurses into the profession to promote positive attitudes.…”
Section: Nurses' Attitudesmentioning
confidence: 99%
“…These findings are supported by a study on nurses' professionalism in Ethiopia, which reported a significant relationship between professionalism and more years of experience. 32 Nurses who have held their jobs for less than four years are likely to still be adjusting to their working environments, which could have a negative effect on their attitudes compared to senior nurses who are more acclimated to their working environments. Nurse leaders may therefore need to be aware of the need to nurture new nurses into the profession to promote positive attitudes.…”
Section: Nurses' Attitudesmentioning
confidence: 99%
“…[16] A cross sectional qualitative study conducted in four different hospitals in Ethiopia, concluded that nurses who joined the professional organization, as well as older nurses had higher professional value scores. [17] It was also determined that involvement in professional organizations improves nurses' perception of their own professionalism while contributing to the growth of the organization. [16,18] …”
Section: Membership In Professional Organizationmentioning
confidence: 99%
“…The mean score of nurses' job satisfaction in the three hospitals indicated that nurses scored low on job satisfaction, 36 – 108 range (24). Previous studies found lower job satisfaction in public sector health workers in both lower and higher-income countries (33, 34). Furthermore, compared to Tikur Anbesa and Jimma University specialized teaching hospitals, nurses working in Ayder Specialized Teaching Hospital showed the lowest job satisfaction.…”
Section: Discussionmentioning
confidence: 73%